Temporal and Spatial Trend of Climate Variability in Vietnam - Nguyen, Duc Luong (Review of Environment and Earth Sciences, 2014)
Vietnam’s long coastline, geographic location, and diverse topography and climates contribute to its being one of the most hazard-prone countries of the Asia-Pacific region. Given that a high proportion of the country’s population and economic assets are located in coastal lowlands and deltas, Vietnam has been ranked among the five countries likely to be most affected by global climate change. This paper aims at providing a short overview on the temporal and spatial trends of climate variability in Vietnam which affected by global climate change.